Aktivitas Guru Matematika dalam Pembelajaran Menggunakan Perangkat Lunak Geometri Dinamis - Tomi Listiawan (Jurnal Elemen, 2020)
This study aims to describe the use of dynamic geometry software (DGS) by mathematics teachers in their teaching and learning activities. This study case involves two junior high school mathematics teachers who use DGS in their teaching activities. The data of this study were collected by recording teacher activity and interviewing the teachers. The data were then analyzed through data transcription, data categorization, data reduction, data review and analysis, and conclusion. The results of this study involved, first, the use of DGS in teaching and learning activities can be categorized into two activities: 1) shifting and 2) delivering content. The delivering content is later divided into two activities: a) applying representation and b) modeling. Shifting activity occurred when teachers had an interval period while conducting one activity to another. Delivering content-applying representation activity occurred when teachers were using DGS to deliver both conceptual and procedural materials to the students. Delivering content-modeling activity occurred when teachers were using DGS to make students acquire knowledge and have a problem-solving skill as performed by their teachers. The modeling activities occurred either explicitly and implicitly.